DESKRIPSI KOMPETENSI PEDAGOGIK GURU GEOGRAFI TENTANG PENILAIAN AUTENTIK SMA NEGERI 2 KOTA PADANG - mariyatun fuji astuti; Khairani Khairani (JURNAL BUANA, 2020)
This article was written to find out the geography teacher's pedagogical competencies regarding authentic assessment of SMA Negeri 2 Kota Padang, as well as the obstacles faced by geography subjects in applying authentic assessment at SMA Negeri 2 Kota Padang. This research method is a descriptive study with a qualitative approach. In this qualitative study there are informants, who were determined using the Purposive Sampling technique. The informants that the researchers took were 4 Geography teachers, Waka Curriculum and School Principal 2 Padang City High School. The results of this study can be seen that the SMA Negeri 2 Kota Padang is one of the leading schools in the City of Padang, which has been implementing authentic assessments since 2013. Socialization and training have been carried out by the principals of the SMA Negeri 2 Kota Padang schools, during the initial implementation of the authentic assessment. However, it is found out in the field that there are obstacles for subject teachers in the application of authentic assessments such as the documentation or archiving process. For the completeness of authentic assessment documents by geography subject teachers, there are still many teachers who provide an assessment of learning outcomes in general for their students. In other words, the application of the authentic assessment has not been going well by the geography teacher at SMA Negeri 2 Kota Padang. and there are still teachers who have not conducted authentic assessments according to the procedures set out in this 2013 curriculum.